Atlas of Ultrasound-Guided Procedures in Interventional Pain Management - Narouze, Samer N. (Springer New York : Imprint: Springer, 2011)
Atlas of Ultrasound-Guided Procedures in Interventional Pain Management is the first book devoted to the new, rapidly expanding field of ultrasound-guided pain medicine (USPM).   It is aimed at physicians who manage acute and chronic pain syndromes who are beginning to use US-guided pain procedures and would like to shorten their learning curve.  Among the target groups are pain physicians, anesthesiologists, physiatrists, rheumatologists, neurologists, orthopedists, sports medicine physicians, spine specialists, and interventional radiologists.   Features:    ·         Step-by-step guidance from the world's leading USPM experts in their area of subspecialty expertise ·         Coverage of acute perioperative pain, chronic pain clinic settings, and MSK applications ·         Sections on spine injections; abdominal and pelvic blocks; peripheral nerve blocks and continuous catheters; and MSK ultrasound •        Tips for improving needle visibility under US (e.g., choosing and applying the transducer;  introducing the needle; and confirming appropriate needle placement) •        Essentials of US knobology ·         Sonoanatomy relevant to peripheral nerve blocks, muscle and joint injections ·         Beautifully illustrated spine sonoanatomy chapter ·         465 figures, 350 of which are in full color    .